2010
DOI: 10.1159/000322861
|View full text |Cite
|
Sign up to set email alerts
|

Mild Campomelic Dysplasia: Report on a Case and Review

Abstract: while in other populations a birth prevalence of 1 in 200,000 has been estimated [Mansour et al., 1995]. Most cases are due to mutations in the SOX9 gene -a member of the SOX (SRY-related HMG box) gene family -located on 17q23-qter, which plays a role in chondrogenesis and sex determination [Foster et al., 1994;Wagner et al., 1994]. In few patients, chromosomal rearrangements involving the cis-regulatory elements upstream of the gene and deletions upstream of SOX9 have also been reported [Wirth et al., 1996;Po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 58 publications
0
7
0
1
Order By: Relevance
“…There are few reports describing non‐lethal CD patients with mutations within the coding region of the SOX9 gene (Table ). Corbani et al [] and Wada et al [] presented the same missense mutation (p.P170L) within the HMG domain protein in a 10.5‐year‐old girl and an 11.5‐tear‐old boy with a mild phenotype of CD. Recently, Okamoto et al [] reported two novel frameshift mutations of the SOX9 coding region in two surviving CD patients, despite putative severely impaired SOX9 proteins.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…There are few reports describing non‐lethal CD patients with mutations within the coding region of the SOX9 gene (Table ). Corbani et al [] and Wada et al [] presented the same missense mutation (p.P170L) within the HMG domain protein in a 10.5‐year‐old girl and an 11.5‐tear‐old boy with a mild phenotype of CD. Recently, Okamoto et al [] reported two novel frameshift mutations of the SOX9 coding region in two surviving CD patients, despite putative severely impaired SOX9 proteins.…”
Section: Discussionmentioning
confidence: 96%
“…Recent published reports described that some long‐term survivors with CD share common skeletal and facial features to SPS including patellar aplagia or hypoplasia, defective ischio‐pubic junction ossification, hypoplastic lesser trochanters, sandal gaps, micrognathia/retrognathia, and cleft palate [Corbani et al, ]. The great phenotypic similarity of surviving CD and SPS requires careful assessment to differentiate the disorders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides micrognathia, which was present in both cases we describe, other facial anomalies have been reported, including large head, flat nasal bridge, as well as low‐set ears. Furthermore, a narrow chest, congenital dislocation of the hip, and bilateral talipes equinovarus are often common (Corbani et al, ). Cardiac anomalies are present in one third of cases.…”
Section: Discussionmentioning
confidence: 99%
“…The phenotype of Fstl1 KO mice is comparable to a rare genetic disorder known as Campomelic Dysplasia (CD; OMIM 114290) (Mansour, Hall, Pembrey, & Young, ). In the majority of CD cases, the underlying cause is a loss of function of one SOX9 allele (OMIM 608160) (Corbani et al, ). However, in approximately 5% of CD cases, no underlying genetic cause can be identified (Unger, Scherer, & Superti‐Furga, ).…”
Section: Introductionmentioning
confidence: 99%